s the work shown below correct? Explain your answer. (11 + 2i ) – (3 – 10i ) = 11 + 2i – 3 – 10i = (11 – 3) + (2i – 10i) = 8 – 8i

Respuesta :

No, because [tex]-(3-10i)=-3+10i[/tex]

Answer:

Given that: [tex](11+2i)-(3-10i)[/tex]

Remove the parentheses, we have;

[tex]11+2i-3+10i[/tex]

Like terms are those terms which have same variables to the same power.

Combine like terms of a constant variable;

[tex](11-3) +2i+10i[/tex]

Similarly, combine like terms of imaginary part, we have;

[tex](11-3) +(2i+10i)[/tex]

Simplify:

[tex]8 +(12i)[/tex]

or

[tex]8+12i[/tex]

Therefore, the correct solution of [tex](11+2i)-(3-10i)[/tex] = [tex]8+12i[/tex]

ACCESS MORE